2018
DOI: 10.3390/languages3020021
|View full text |Cite
|
Sign up to set email alerts
|

Typological Differences in Morphological Patterns, Gender Features, and Thematic Structure in the L2 Acquisition of Ashaninka Spanish

Abstract: It has been widely argued that morphological competence, particularly functional morphology, represents the bottleneck of second language acquisition (Jensen et al. 2017;Lardiere 1998Lardiere , 2005Slabakova 2008Slabakova , 2009Slabakova , 2013. In this study, we explore three challenging aspects of the morphology of Spanish among advanced L1 Ashaninka-L2 Spanish speakers: (i) the acquisition of proclitics and enclitics with inflected verbs; (ii) the distribution of accusative clitics according to the thematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(36 reference statements)
0
1
0
5
Order By: Relevance
“…Rosa Vallejos distingue entre el español amazónico de hablantes nativos de español con el hablado por hablantes con sustrato kokama (iso 639-3: cod, familia lingüística tupi-guaraní) (Vallejos 2014). En un estudio centrado en los enclíticos y el grado de leísmo, Liliana Sánchez y Elisabeth Mayer contrastan el español amazónico entre hablantes con sustrato asháninka (iso 639-3: cni, familia lingüística arawak) y hablantes nativos de español en la región Junín, también parte de la Amazonía peruana (Sánchez y Mayer 2018). Finalmente, Napurí revisa la presencia del doble posesivo en variedades de español amazónico con sustrato asháninka y sustrato bora (iso 639-3: boa, familia lingüística bora) (Napurí 2018).…”
Section: íNdiceunclassified
See 2 more Smart Citations
“…Rosa Vallejos distingue entre el español amazónico de hablantes nativos de español con el hablado por hablantes con sustrato kokama (iso 639-3: cod, familia lingüística tupi-guaraní) (Vallejos 2014). En un estudio centrado en los enclíticos y el grado de leísmo, Liliana Sánchez y Elisabeth Mayer contrastan el español amazónico entre hablantes con sustrato asháninka (iso 639-3: cni, familia lingüística arawak) y hablantes nativos de español en la región Junín, también parte de la Amazonía peruana (Sánchez y Mayer 2018). Finalmente, Napurí revisa la presencia del doble posesivo en variedades de español amazónico con sustrato asháninka y sustrato bora (iso 639-3: boa, familia lingüística bora) (Napurí 2018).…”
Section: íNdiceunclassified
“…Liliana Sánchez y Elisabeth Mayer revisan otra característica llamativa del español amazónico: la presencia del pronombre le para construcciones con objeto directo entre hablantes de español amazónico con sustrato asháninka y hablantes nativos de español en territorio amazónico (Sánchez y Mayer 2018). Ellas centran su trabajo en los distritos de Puerto Ocopa y Satipo en la región Junín.…”
Section: Los Distintos Españoles Amazónicos: Una Serie De Precisionesunclassified
See 1 more Smart Citation
“…Previous studies on bilingual language acquisition within a formal perspective have extensively reported crosslinguistic influence effects in morphosyntactic properties that differ typologically or that lie at the interfaces between syntax and other cognitive components (Montrul, 2004(Montrul, , 20082010b;Pirvulescu et al, 2014;Sánchez and Mayer, 2018;Sorace, 2011). The advantages in the acquisition of morphosyntactic properties of HSs over L2 learners have been extensively documented (Cuza and Frank, 2015;Montrul, 2005Montrul, , 2010b, but also the disadvantages (Montrul, Foote and Perpiñán, 2008).…”
Section: Previous Research 1 Spanish Se In L2 Learners and Heritage S...mentioning
confidence: 99%
“…En efecto, la lengua importada de Europa ha tenido, en la región oriental peruana, una evolución peculiar debido a múltiples factores (Escobar 1978: 75), entre los cuales destacan el aislamiento del resto del país, su condición periférica con respecto a los centros políticos y administrativos, los lazos con las regiones colindantes occidentales (los contactos con los lusohablantes de Brasil) y, sobre todo, el influjo a nivel de sustrato de las numerosas lenguas originarias (Solís 2009: 317;Napurí 2018: 192;Emlen 2016;Mayer y Sánchez 2016;Sánchez y Mayer 2018), en particular del quechua, usado en la época de las misiones como lengua franca (García [1987] 2015: 5; Marticorena 2010) 1 , sobre todo en la actual región Loreto.…”
Section: Introductionunclassified